Concepts Important to Patients With Facial Differences: A Qualitative Study Informing a New Module of the FACE-Q for Children and Young Adults. (August 2021) - Kamran, Rakhshan; Longmire, Natasha M.; Rae, Charlene; Riff, Karen W. Y. Wong; Forrest, Christopher R.; O'Hara, Justine; Bulstrode, Neil; Klassen, Anne F.
Objective: The concepts important to children and young adults who undergo treatments for facial differences are not well-defined. Measurement of treatment outcomes from the patient's perspective is necessary to ensure goals of treatment are met. We aimed to identify concepts important to children and young adults with facial differences through a qualitative study. Design: An interpretive description qualitative approach was followed. Semistructured interviews were conducted, transcribed verbatim, and coded using a line-by-line approach. Qualitative analysis led to the development of a conceptual framework of outcomes important to patients. Setting: Interviews were conducted in Canada and the United Kingdom at home, by telephone, or in the hospital. Participants: Participants (N = 72) were recruited between May and June 2014 from craniofacial clinics at the Hospital for Sick Children (Toronto) and Great Ormond Street Hospital (London). Participants included anyone with a visible and/or functional facial difference aged 8 to 29 years and fluent in English, excluding patients with a cleft. The sample included 38 females and 34 males, with a mean age of 13.9 years, and included 28 facial conditions (11 facial paralysis, 18 ear anomalies, 26 skeletal conditions, and 17 soft tissue conditions). Results: Analysis led to identification of important concepts within 4 overarching domains: facial appearance, facial function, adverse effects of treatment, and health-related quality of life (psychological, social, and school function). Conclusions: Our study provides an understanding of concepts important to children and young adults with facial differences.